2008
DOI: 10.1161/circulationaha.108.788166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, Treatment, and Control of Hypertension in China

Abstract: One in 6 Chinese adults is hypertensive, but only one quarter are aware of their condition. Despite increased rates of blood pressure-lowering treatment, few have their hypertension effectively controlled. National hypertension programs must focus on improving awareness in the wider community, as well as treatment and control, to prevent many tens of thousands of cardiovascular-related deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
354
22
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(417 citation statements)
references
References 29 publications
38
354
22
3
Order By: Relevance
“…Similar to other studies, 21,24,26 our results demonstrated that hypertension was more prevalent among women than men and increased with age for both genders, though the increase was more pronounced among women than men. Hormonal factors, postmenopausal weight gain, and a different risk profile might account for the higher age-specific prevalence rates of hypertension among women compared with men.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to other studies, 21,24,26 our results demonstrated that hypertension was more prevalent among women than men and increased with age for both genders, though the increase was more pronounced among women than men. Hormonal factors, postmenopausal weight gain, and a different risk profile might account for the higher age-specific prevalence rates of hypertension among women compared with men.…”
Section: Discussionsupporting
confidence: 92%
“…This rate exceeds that reported in other developing countries in the region (for example, Egypt (26.3%), Cameroon (15%), Ghana (29.4%)), [21][22][23] as well as that reported in developed countries in Asia (for example, China (20%), Pakistan (20.7%), Saudi Arabia (26.1%), Malaysia (27.8%)). [24][25][26][27] The rate remains lower than that in the developed countries of Europe (for example, Italy (38%), United Kingdom (42%), Spain (47%), Romania (44.9%), Germany (55%)) and the United States (56%)). 28,29 Our findings further substantiate the results of sustained and integrated economical, social and health development in Tunisia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Data from the 2002 China National Nutrition and Health Survey showed that 14?7 % of Chinese were overweight and another 2?6 % were obese, which translates into 184 million overweight and 31 million obese people in China (2) . The epidemic of obesity and overweight has become a public health issue and is an important health risk for diseases like diabetes, high blood pressure, atherosclerosis and others (3) .…”
mentioning
confidence: 99%
“…Data from 2002 China National Nutrition and Health Survey show that 21.8% of Chinese are overweight (body mass index (BMI) X25 kg/m 2 ) and 18.8% of Chinese are hypertensive, such that there are currently (2002) 195 million overweight people and 160 million hypertensive people in China out of a total of 1.3 billion population (Wu, 2006;Wu et al, 2008). Hypertension and overweight are both growing epidemics with the rapid socioeconomic development in China.…”
Section: Introductionmentioning
confidence: 99%